Diálogo, conflito e jogos retóricos do poder no processo de regularização do território quilombola alto trombetas em Oriximiná (PA) - MENDES, Raiana Siqueira (2022)
The general objective of this article is to reflect on the uses of the notion of "dialogue", as a native and analytical category, in the context of meetings in which alternatives were sought to reconcile the territorial right of the communities represented by the Association of Quilombo Remnants Communities of Alto Trombetas II (ACRQAT) and the diffuse right to the environment, in this case specifically applied to two federal Conservation Units managed by the Chico Mendes Institute for Biodiversity Conservation (ICMBio). While ACRQAT was claiming title to the quilombola territory of Alto Trombetas II, the ICMBio was defending the management of the Saracá-Taquera National Forest and of the Trombetas River Biological Reserve, in the context of an administrative process, (opened in 2004 at INCRA) permeated by the conflict resulting from the territorial overlap between the quilombola territory and the conservation units. We seek to understand what the dialogue consists of and in which situations it is triggered. We also investigated if the characteristics of the negotiation process about the land regularization of the territory are, effectively, dialogic. The work is based on observations made through ethnographic fieldwork between 2015 and 2018, plus a literature review of the productions of classical and contemporary authors on the proposed theme, considering the polysemy of the term "dialogue", as well as documentary research, in order to analyze the documents issued during the process in question, such as memories, reports, ordinances, technical notes, minutes of meetings and others. Thus, as occurs in the REURB processes that we have verified throughout this course, from distinct processes, the dialogue is a fundamental part to promote improvements in the land regularization policies, we hope with this work, to be able to contribute with the debates, also proposing new interventions for the Amazon Network.